The eradication of smallpox : Edward Jenner and the first and only eradication of a human infectious disease - Bazin, H. (Academic Press, 2000)
Simply, and with great humanity, The Eradication of Smallpox tells the story of smallpox - it's origins, the horror of the disease, and the millions of people killed or disfigured by it. During the 18th and 19th centuries, it is estimated that one out of every ten people died from the disease; some say one out of every seven. Smallpox attacked very young children in particular. The story progresses with the practice of variolation, the life of Edward Jenner who first proposed 'vaccination' with cow pox vaccine (little James Phipps was the first person ever vaccinated in this way), the years of debate about the efficacy of this novel method, and the later worldwide initiatives to rid the planet of this horrific disease. In 1979, the story culminates in the only total eradication of an infectious disease that mankind has ever accomplished. This year celebrates the 20th anniversary of this momentous achievement. In the intervening years, debate has raged about what we should do with the remaining smallpox viral stocks. Do we destroy them, so they can't fall into the hands of bioterrorists, or do we maintain them, in case they may be of use in some unexpected way, for therapeutic purposes? These questions are thoroughly discussed in the book. Key Features * Covers the background, history and origin of smallpox, and brings the story up to the present day * Gives full and interesting details of Jenner's life, and tells how this humble country doctor brought about a revolution in vaccination * Includes many quotes from historical figures * Features 120 high quality photographs, many originating from unique historical plates in the author's private collection * Includes new research data * Provides new views on the eradication and destruction of smallpox.